2019
DOI: 10.1016/j.chemosphere.2019.05.281
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations of perfluoroalkyl substances partitioning between surface water, suspended sediment, and biota in a macrotidal estuary

Abstract: A temporal follow-up of PFAS partitioning was conducted in a macrotidal estuary. • Mean ΣPFASs = 6.5 ng L-1 in water, 3 ng g-1 in SPM, and 6.4 ng g-1 in invertebrates. • PFAS levels and profiles were relatively stable across different seasons. • Chain length was the key controlling factor of PFAS sorption and bioaccumulation. • Partitioning coefficients and bioaccumulation factors varied within a limited range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Conversely, high values of log 10 BAF were calculated for small crustacean (mysids and copepods) in France estuarine area. In particular, in the whole body, the highest value was detected for L-FOSA (4.1 for copepods and 4.9 for mysids), confirming the great threat of PFCs due to their bioaccumulation (and biomagnification) potential also in small organisms [85]. Conversely, a biomonitoring screening conducted on different aquatic organisms and tissues in Vietnam, reported that BCF values in seven fish species were always higher in the liver (max BCF value found in tilapia for heneicosafluoroundecanoic acid (PFUnDA) of 142,764 L/kg followed by PFDA of 22,953 L/kg, PFDoA of 7729 L/kg, and PFOS of 3551 L/kg) than in the muscles (max BCF value found in tilapia for PFUnDA of 9169 L/kg) and the whole body (max BCF value found in dusky sleeper for PFNA of 1627 L/kg) [99].…”
Section: Biomonitoring Pfas In Aquatic Faunamentioning
confidence: 81%
See 1 more Smart Citation
“…Conversely, high values of log 10 BAF were calculated for small crustacean (mysids and copepods) in France estuarine area. In particular, in the whole body, the highest value was detected for L-FOSA (4.1 for copepods and 4.9 for mysids), confirming the great threat of PFCs due to their bioaccumulation (and biomagnification) potential also in small organisms [85]. Conversely, a biomonitoring screening conducted on different aquatic organisms and tissues in Vietnam, reported that BCF values in seven fish species were always higher in the liver (max BCF value found in tilapia for heneicosafluoroundecanoic acid (PFUnDA) of 142,764 L/kg followed by PFDA of 22,953 L/kg, PFDoA of 7729 L/kg, and PFOS of 3551 L/kg) than in the muscles (max BCF value found in tilapia for PFUnDA of 9169 L/kg) and the whole body (max BCF value found in dusky sleeper for PFNA of 1627 L/kg) [99].…”
Section: Biomonitoring Pfas In Aquatic Faunamentioning
confidence: 81%
“…Biomagnification phenomena have been evaluated also in Gironde Estuary (France) based on PFCs concentrations found in mysids and copepods with BMF > 1 for PFOS, perfluorooctanesulfonamide (FOSA), and long-chain perfluorinated carboxylic acids (PF-CAs) [85]. Trophic magnification was also proven in urban river environment (Orge, France) with values of TMFs > 1 for C 9 -C 14 PFCA, C 7 -C 10 PFSAs and several PFAAs such as sulphonated fluorotelomers 8:2 and 10:2) [86].…”
Section: Bioaccumulation In Aquatic Faunamentioning
confidence: 99%
“…While decreases in PFNA and PFUnA concentrations were observed in fish fillet during the time period of this study, changes in concentrations of other PFAAs were variable. The numerous factors determining the fate, bioaccumulation, and trends of PFAS in the environment are yet to be fully understood (Babut et al 2017; Taylor et al 2018; Munoz et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In Italian lakes, which were studied in the present work, the seasonal trend was much stronger for the chlorinated compounds than for PFAS. Variations in PFAS were quite limited, as in the Gironde estuary, where PFAS only varied up to a factor of 2.5× for zooplankton and 2.3× for shrimps in different seasons [49].…”
Section: Role Of Zooplankton Size and Seasonality On Contaminant Levelsmentioning
confidence: 99%